Technical and training related aspects of resistance training using blood flow restriction in competitive sport - A review - Wilk, M.; Krzysztofik, M.; Gepfert, M.; Poprzecki, S.; Golas, A.; Maszczyk, A. (Journal of Human Kinetics, 2018)
Blood flow restriction (BFR) combined with resistance training (RT-BFR) shows significant benefits in terms of muscle strength and hypertrophy. Such effects have been observed in clinical populations, in groups of physically active people, and among competitive athletes. These effects are comparable or, in some cases, even more efficient compared to conventional resistance training (CRT). RT-BFR stimulates muscle hypertrophy and improves muscle strength even at low external loads. Since no extensive scientific research has been done in relation to groups of athletes, the aim of the present study was to identify technical, physiological and methodological aspects related to the use of RT-BFR in competitive athletes from various sport disciplines. RT-BFR in groups of athletes has an effect not only on the improvement of muscle strength or muscle hypertrophy, but also on specific motor abilities related to a particular sport discipline. The literature review reveals that most experts do not recommend the use RT-BFR as the only training method, but rather as a complementary method to CRT. It is likely that optimal muscle adaptive changes can be induced by a combination of CRT and RT-BFR. Some research has confirmed benefits of using CRT followed by RT-BFR during a training session. The use of BFR in training also requires adequate progression or modifications in the duration of occlusion in a training session, the ratio of exercises performed with BFR to conventional exercises, the value of pressure or the cuff width. Keywords: occlusion; resistance exercise; training variables; sports performance